أصوات الحركات العربية: دراسة دلالية جمالية - نجار، منال محمد هاشم (جامعة مؤتة - عمادة البحث العلمي, 2010)
يعرض هذا البحث عناية علماء العربية القدامى بطبيعة العلاقة بين حركات الألفاظ ومعانيها ودورها في تحقيق جمال اللفظ وما تبعثه من متعة. \ اهتم علماء اللغة والنحو بهذين البعدين ، فجاءت آراؤهم مبثوثة في كتبهم مختلفة الاختصاصات؛ فهم في الغالب يجعلون الضمة التي هي أقوى الحركات للمعنى الأقوى ، والفتحة الخفيفة للمعنى الخفيف والكسرة للمعنى المتوسط. \ وهم أيضاً يستخدمون الفروق بين الفتحة من ناحية والكسرة والضمة من ناحية أخرى في تأليف اللفظة ، لتحقيق غايات جمالية على المستوى الصوتي معتمدين حسهم اللغوي. \ درست هذه الآراء وفق رؤية جديدة ، قوامها الإحساس بحركة اللفظة دلالياً وجمالياً، انطلاقاً من مخارج هذه الحركة وخصائصها النطقية التي ارتآها الدرس الصوتي الحديث مع المناقشة والتحليل، وزوت البحث بعرض آراء الدارسين المعاصرين ومواقفهم من طبيعة هذه العلاقة. A deliberate and thorough reading is required to deal with this research in the Arabic language which is self-evident of being able to stimulate readers' imagination, elevate their taste and arouse their senses. \ This research highlights the relationship examined by old Arabic scholars between the Arabic diacritical marks (short vowels), their meanings and role in realizing the beauty of the word. The studies of old scholars focused on these two dimensions varying in views in line with their various specializations and concerns. According to them, the short vowel /u/ (aldamma) is considered to be the strongest vowel and thus used for expressing strong meanings, while the short vowel /a/ (alfatha) expresses light or simple meanings; the short vowel /i/ (alkasra), on the other hand, expresses meanings of moderate effect. \ Furthermore, Old Arabs used to employ the differences that exist between alfatha on the one hand and between askasra and aldamma on the other hand to build up the word with a view to creating aesthetic purposes on the phonetic level relying on their own linguistic competence and understanding. \ All previous literature in this regard has been examined in accordance with a new perspective aiming at capturing the semantic as well as the artistic dimensions of the diacritical marks of a word. In applying this approach, the research adopted, analyzed and discussed points of articulation of each diacritical mark and its articulatory characteristics as stated in modem phonetics. The research, moreover, provides a review of opinions and attitudes of contemporary scholars interested in the relation between the sounds of diacritical marks and their meanings.
Keywords: معاني الألفاظ -- اللغة العربية -- النحو -- علم الاصوات اللغوية -- مخارج الحروف -- حركات الإعراب -- الدلالة النحوية -- دلالة الألفاظ -- الأفعال -- التراكيب اللغوية